A subtle economy of time: Social media and the transformation of Indonesia's Islamic preacher economy. Issue 1 (January 2017) - Slama, Martin
Abstract: The article is concerned with the latest developments in Indonesia's Islamic field. Its focus is on the role of social media in exchange relationships between Islamic preachers and their constituency. The article first discusses economic exchanges between preachers and their followers, and then it concentrates on social exchanges and how they are mediated today. Empirically, the article delivers insight into the concerns of mostly female Indonesian middle‐class Muslims and shows how preachers have to adjust to the needs of their followers who are regularly online. Theoretically, the article offers a rereading of Pierre Bourdieu's classic work on forms of capital and their conversion. It emphasizes the temporal dimension of capital accumulation and conversion and explores the temporalities of online exchanges that have become constitutive of preacher–follower relationships. In doing so, it shows how Indonesia's Islamic preacher economy is currently transformed by these online exchanges, resulting in preacher–follower relationships that are characterized by dialogic constructions of Islamic authority. Being part of Indonesia's Islamic field, these changes in the Islamic preacher economy point to a broader trend in Indonesia's Islamic field toward greater sensitivity to the needs and worries of Indonesian middle‐class Muslims.